Ancient DNA extraction methods for herbarium specimens: When is it worth the effort? - Marinček, Pia; Wagner, Natascha D.; Tomasello, Salvatore (Applications in plant sciences, 2022)
Premise Herbaria harbor a tremendous number of plant specimens that are rarely used for molecular systematic studies, largely due to the difficulty in extracting sufficient amounts of high‐quality DNA from the preserved plant material. Methods We compared the standard Qiagen DNeasy Plant Mini Kit and a specific protocol for extracting ancient DNA (aDNA) (the N‐phenacylthiazolium bromide and dithiothreitol [PTB–DTT] extraction method) from two different plant genera (Xanthium and Salix). The included herbarium materials covered about two centuries of plant collections. To analyze the success of DNA extraction using each method, a subset of samples was subjected to a standard library preparation as well as target‐enrichment approaches. Results The PTB–DTT method produced a higher DNA yield of better quality than the Qiagen kit; however, extracts from the Qiagen kit over a certain DNA yield and quality threshold produced comparable sequencing results. The sequencing resulted in high proportions of endogenous reads. We were able to successfully sequence 200‐year‐old samples. Discussion This method comparison revealed that, for younger specimens, DNA extraction using a standard kit might be sufficient. For old and precious herbarium specimens, aDNA extraction methods are better suited to meet the requirements for next‐generation sequencing.